A pragmática dos dogwhistles: algumas questões - Santos, Pedro (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
Dogwhistles are communicative mechanisms for expressing subliminal meanings. In this paper, I take up the distinction, usual in the literature on the topic, between two types of dogwhistle: overt and covert, whereby in the latter, as opposed to the former, the preservation of the subliminal character of the message seems to be a necessary condition for the dogwhistle’s communicative success. I discuss various aspects of this distinction, arguing that both types of dogwhistle can be analysed as conversational implicatures bearing in mind, in particular, the canonical properties of cancelability and calculability.